Corporate Governance Recent Advances and Perspectives - Lawrence Emeagwali, Okechukwu; Bhatti, Feyza (IntechOpen, 2022)
Corporate Governance - Recent Advances and Perspectives is a comprehensive overview of recent developments in business, management and economics. Chapters cover such topics as agency theory and internationalization, Corporate Social Responsibility, COVID-19 and corporate governance performance, gender diversity and corporate governance, and much more.